The Influence of Organizational Culture and Leadership on Work Productivity at The Intelligence and Security Agency (Baintelkam) of The Republic of Indonesia Police - Agus Andrianto; Harries Madiistriyatno; Nurwulan Kusumadewi (Dinasti International Journal of Management Science, 2026)
This study aims to determine the influence of organizational culture on work productivity, the influence of leadership on work productivity, the influence of work discipline on work productivity, the influence of work discipline on work productivity, the influence of work discipline on organizational culture on work productivity, and the influence of work discipline on leadership on work productivity of Indonesian National Police (Baintelkam Polri) personnel. Based on the Sobel test, a Z-value of 0.59 was obtained, which is less than the critical value of 1.96 at the 5 percent significance level. These results indicate that Work Discipline (Z) does not significantly mediate the influence of Organizational Culture (X1) on Work Productivity (Y). Based on the Sobel test, a Z-value of 3.91 was obtained, which is greater than the critical value of 1.96 at the 5 percent significance level. These results indicate that Work Discipline (Z) significantly mediates the influence of Leadership (X2) on Work Productivity (Y).